Diversity of aphid pests on the crops in Kanchanpur district, Nepal - Bista, Mahadev (Journal of Natural History Museum, 2020)
A survey was conducted to explore the aphid pests’ diversity in Kanchanpur district, far-western, Nepal from April 2018 to March 2019. A total of 15 aphid pests were collected and identified, viz. Acyrthosiphon pisum (Harris), Aphis craccivora (Koch), Aphis gossypii (Glover), Aphis fabae (Scopoli), Aphis nerii Boyer de Fonscolombe, Brevicoryne brassicae (Linnaeus), Lipaphis erysmi (Kaltenbach), Macrosiphum euphorbiae (Thomas), Macrosiphum rosae (Linnaeus), Myzus persicae (Sulzer), Rhopalosiphum maidis (Fitch), Rhopalosiphum padi (Linnaeus), Rhopalosiphum rufiadominale (Sasaki), Uroleucon compositae (Theobald), and the guava aphid. Exploration of aphid pests showed that they caused serious damages to agricultural crops by attacking different parts of plants.